Technological and socio-economic analysis of the local production system of the pink Zaragoza bean (Phaseolus vulgaris L.) in the Caribbean of Colombia - Martínez-Reina, Antonio María; Grandett-Martínez, Liliana María; Tordecilla-Zumaqué, Lilibet; Rodríguez-Pinto, María del Valle; Cordero-Cordero, Carina Cecilia; Tofiño-Rivera, Adriana Patricia (Sociedad Colombiana de Ciencias Hortícolas-SCCH and Universidad Pedagógica y Tecnológica de Colombia-UPTC, 2021)
The objective of this study was to characterize the Zaragoza pink bean production system in the Colombian Caribbean from the technical and economic point of view. A survey was randomly applied to 32 farmers in producing areas. The data were analyzed using descriptive statistics, measurements of central tendency and contingency tables. The economic return calculations were made using a production cost pattern and economic profitability analysis techniques. The results showed that the average experience in cultivation is 12 years; the average age of the farmers is 48 years; the predominant type of tenure is property in 63% of the sample; and the mode of the area devoted to this crop is 0.5 ha. The use of family labor predominates in 65% of cases. 90% of the production is destined for the market, 8% is destined for self-consumption, and 2% is for seeds. Production costs correspond to 1,437 USD/ha, the average production is 1,700 kg ha-1, and the average sale price was 0.886 USD/kg, which generates a cost benefit ratio of 1.43% in three months of the productive cycle, from sowing to postharvest. This crop is profitable and stable inasmuch as its yields recover costs and generate profits for producers.